P82 The use of dry blood spot testing for hepatitis C in injecting drug users attending substance misuse services. (16th November 2010) - Tait, J; Stephens, B; O'Keeffe, S; Dillon, J
Abstract : Introduction: Diagnosing hepatitis C virus (HCV) in current injecting drug users has often proved challenging. This is due to the individual's reluctance to attend hospital clinics, lack of testing in substance misuse services and poor venous access. Dry blood spot testing (DBST) has proven to be a robust and easy method of determining HCV status which can be carried out by staff working in Drug Services. Aim: The aim of this study was to evaluate the ease of use of DBST in clinical practice. Method: The study was carried out between August 2009 and April 2010. Staff within local substance misuse services were given appropriate training in the use of DBST. Testing for HCV was offered to individuals who accessed services during this period. A follow-up appointment was given for 2 weeks after testing and a referral to specialist services was offered to those individuals who tested positive. Results: A total of 361 individuals were tested during the study period. 65.1% (235/361) of the individuals tested were male, the age range was between 18 and 51 years. 73.1% (264/361) were negative for HCV antibodies and 26.8% (97/361) were positive. 93.3% (337/361) attended a follow-up appointment for their results. Of the 88 individuals who received their antibody positive results, all were offered referral to health services to provide further information and check HCV PCR. 6 are awaiting an appointment date and 17 have not attended any follow-up appointment. 79.2% (65/82) have attended a follow-up appointment at specialist services, the prison clinic or their GP to have blood checked for HCV PCR. Results available to date show that 60% (36/60) are PCR positive. Individuals who are PCR negative have been informed they do not require any further follow-up and all PCR positive people have been encouraged to attend drug treatment services and/or offered an appointment at specialist services for assessment of liver disease and treatment. Conclusion: The study has shown DBST is easy to use and can be carried out without difficulty by staff within drug services. The offer of HCV testing was well received by this particular client group with over 90% of individuals returning for their results. Knowing HCV status also allowed staff to reiterate the appropriate harm reduction measures and encourage referral to services for drug treatment. 79% attended a follow-up appointment therefore suggesting that providing BBV testing is valuable in a group who are often envisaged as being too chaotic to engage with health services.